Chinese philosophy in an era of globalization - Wang, Robin (State University of New York Press, 2004)
Annotation This book treats Chinese philosophy today as a global project, presenting the work of both Chinese and Western philosophers. Providing contemporary considerations of the Chinese philosophical tradition and bringing Chinese philosophy into conversation with Western philosophy, "Chinese Philosophy in an Era of Globalization provides a model for collaborative work. Topics covered include value theory, philosophy of religion, human nature, virtue ethics, epistemology, and philosophy of language.
Keywords: Philosophy, Chinese.; Philosophy, Modern -- 20th century.; Philosophy, Modern.; Philosophie chinoise.; Philosophie -- 20e siècle.; PHILOSOPHY -- Eastern.; Philosophy, Chinese; Philosophy, Modern; 1900-1999